Bioprocessing for biofuel production strategies to improve process parameters - Srivastava, Neha 1981-; Srivastava, Manish 1973-; Mishra, P.K; Gupta, Vijai Kumar 1981- (Springer, 2021)
Converting biomass to biofuels involves hydrolyzing cellulose to sugars using cost-intensive commercial enzymes - an expensive step that makes large-scale production economically non-viable. As such, there is a need for low-cost bioprocessing. This book critically evaluates the available bioprocessing technologies for various biofuels, and presents the latest research in the field. It also highlights the recent developments, current challenges and viable alternative approaches to reduce the overall cost of producing biofuels
Chapter 1. Impact of fermentation types on enzymes used for biofuels production -- Chapter 2. Downstream Processing; Applications and Recent Updates -- Chapter 3. Role of bioreactors in bio-fuel generations -- Chapter 4. Bioprocess for Algal Biofuels Production -- Chapter 5. Effect of Bioprocess Parameters on Biofuel Production -- Chapter 6. Role of substrate to improve biomass to bio fuel production technologies -- Chapter 7. Techno-economic analysis of second-generation bio-fuel technologies -- Chapter 8. Recent advances in metabolic engineering and synthetic biology for microbial production of isoprenoid-based biofuels: an overview -- Chapter 9. Applications of biosensors for metabolic engineering of microorganisms and its impact on biofuel production -- Chapter 10. Recent progress in CRISPR-based technologies applications for biofuels production
Keywords: Plant biochemistry; Microbiology; Environmental chemistry; Environmental engineering; Biotechnology; Environmental management